An Evaluation of the Assessment of Graphical Education at Junior Cycle in the Irish System - Delahunty, Thomas; Seery, Niall; Lynch, Raymond (Design and Technology Education: An International Journal, 2012)
Junior Certificate Technical Graphics was introduced in Ireland in 1991 and aimed to develop innovative problem solving aptitudes and knowledge of plane and descriptive geometry (NCCA 1991). Despite the philosophy of breadth and balance (NCCA 2004) associated with educational outcomes in the Junior Certificate curriculum, many subjects, Technical Graphics included, employ a summative assessment strategy (Griffin 1998). The summative measurement model portrays a limited view of student learning (Lin and Dwyer 2006, Williams 2011) and has been found to exert significant influence on teaching and learning throughout the course of study (Bloxham and Boyd 2007). This research study aims to evaluate the types of approach to assessment of two different year groups at different stages of the Junior Cycle. The core hypothesis being investigated is whether there is a more sophisticated approach to the assessment evident among the older year groups. In order to achieve this aim a visual protocol similar to Middleton (2008) and Lane et al. (2010) was employed to capture the approach in solving a prescribed graphical task among first and second year students in the Technical Graphics classroom. Findings indicate that the use of a traditional summative approach to assessment has significant limitations within the subject of Technical Graphics. There are also notable trends occurring in students’ approach to the assessment, which seem to rely on a low level of graphical knowledge and problem solving skills. The findings confirm that the older year group adopted a more efficient approach to the assessment but displayed unsophisticated approaches to the application of graphical principles. Some limitations of the summative measurement model are supported by the results of this paper.